Factors Affecting the Career Choices of Graduating Public Secondary Students in Ligao City Division, Ligao City, Philippines - Babagay-Llacer, Cynthia (Indonesian Journal of Teaching in Science, 2021)
The purpose of the study was to determine the career choices of graduating public secondary students in Ligao City Division, Ligao City, Philippines, and the factors affecting their career choices. This study identified respondents with focused variables on career choices and the factors affecting career choices. The study expanded career choices in different aspects. This study utilized a questionnaire checklist that facilitated the data-gathering through sampling. The findings revealed that out of 976 secondary students, they interested in Tourism and Culinary Arts(18%), Education and Business (17%), Engineering (16%), Science and Technology and in Medical and Health Care (9%), Arts and Design (6%), and Communication and Information Services and Technical Courses (4%). The career choices of the graduating secondary students are influenced by a family (90%), personal interest (77%), and career opportunities(57%), higher education (51%), and the school where they are presently enrolled (49%). The study concludes that the graduating secondary students are interested in the following career choices in descending order: Tourism and Culinary Arts, Education, Business, Engineering, Science and Technology, Medical and Health Care, Arts and Design, Communication and Information Services, and Technical Courses. Results of this study may serve individuals who are involved in teaching or managing secondary schools in terms of strengthening the curriculum and instructions to provide career needs of graduates.